2019
DOI: 10.3390/agriculture9020028
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Environmental Efficiency of Greek Dairy Sheep Farms: GHG Emissions and Mitigation Potential

Abstract: One of the main ecological challenges that agricultural and especially livestock production systems face is the adoption of management practices that encourage the mitigation of greenhouse gas (GHG) emissions, while maintaining their production level. According to the relevant literature, the potential for GHG reduction lies mainly in greater efficiency in meat and dairy production, which suggests that the ecological modernization of livestock farms follows the efficiency/substitution pathway. This study aims … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 29 publications
0
10
1
Order By: Relevance
“…For transhumant sheep and goats, the average farm rearing under 350 ewes-dams operated under net losses of 84.2€/ewe excluding income support [19]. More recently, Sintori et al [53] reported an average milk yield of 136.8 kg/ewe for sheep farms in mainland Greece combining feedstuff provision from markets, crops cultivation and grazing, while Pulina et al [12] presented a considerably lower average milk yield for Greek sheep farms (101 kg/ewe) but higher milk prices (0.96€/kg) than those reported in this study. Better results have been reported for more intensive patterns, for instance positive net profit with considerably higher production costs (390€/ewe) [14] and average milk yield of 276.6 kg/ewe for Chios sheep farms, whose grazing average was close to C1 SF in this study [54].…”
Section: Discussionmentioning
confidence: 99%
“…For transhumant sheep and goats, the average farm rearing under 350 ewes-dams operated under net losses of 84.2€/ewe excluding income support [19]. More recently, Sintori et al [53] reported an average milk yield of 136.8 kg/ewe for sheep farms in mainland Greece combining feedstuff provision from markets, crops cultivation and grazing, while Pulina et al [12] presented a considerably lower average milk yield for Greek sheep farms (101 kg/ewe) but higher milk prices (0.96€/kg) than those reported in this study. Better results have been reported for more intensive patterns, for instance positive net profit with considerably higher production costs (390€/ewe) [14] and average milk yield of 276.6 kg/ewe for Chios sheep farms, whose grazing average was close to C1 SF in this study [54].…”
Section: Discussionmentioning
confidence: 99%
“…The result of these investigations has made it possible to determine how the non-parametric DEA methodology is a research instrument widely used today, and that it is frequently applied to various sectors of the economy [20]. In the specific field of the agrarian economy, the contributions of Karimov [21], Niavis et al [22], Jalilov et al [23], Arru et al [24], Sintori, Liontakis, and Tzouramani [25], Mengui, Oh, and Lee [26], Havlíček et al [27], Gołaś et al [28], Fernández-Uclés et al [29], Işgın et al [30], and Bahta, Jordaan, and Sabastain [31] were identified.…”
Section: Methodsmentioning
confidence: 99%
“…Then, the improvements of the efficiency are more needed in the recreational services subsector. In the study of Sintori, Liontakis, and Tzouramani [25], the management practices that encourage the mitigation of greenhouse gas (GHG) emissions in the Greek rural economy were analysed. Data analysis was carried out with the aid of DEA methodology, revealing that the technical and environmental efficiency of sheep farms are tied.…”
Section: Methodsmentioning
confidence: 99%
“…To our knowledge, this is the first study that uses efficiency analysis to increase knowledge on best practices that could be potentially introduced to sheep farms as innovations. Regarding the European small ruminant sector, the studies on efficiency are limited in the estimation of the level of technical efficiency of the farms and the detection of the sociodemographic and environmental factors that explain efficiency differentials (indicatively see [2,[23][24][25][26][27][28][29]). Moreover, all of these studies are focused on the dairy sheep sector; only Perez et al [23] estimated the efficiency level on the sheep meat sector, without, however, providing insights regarding the structural and economic characteristics of the efficient farms.…”
Section: Introductionmentioning
confidence: 99%